The application of the Groebner Basis technique in power flow study - Jiaxin Ning; Wenzhong Gao; Radman, Ghadir; Liu, Jane (2009 North American Power Symposium, 2009)
Power flow study is one of the most dominant subjects in the field of power system. This paper applies the Groebner Basis (GB) technique to solve power flow problem. The GB technique is a systematic mathematical tool to solve nonlinear polynomial algebraic equations. The technique has capabilities of uncoupling any given set of coupled equations. Uncoupling not only facilitates numerical work, but also provides the possibility of solving uncoupled equations of up to the fifth degree analytically in symbolic form. For higher degree, since the new set of equations is decoupled, the overall solution is simplified. The superior property of the technique brings an alternative method for power flow study. 3-bus and 5-bus power system are used to test and discuss the GB technique. The effectiveness of this technique is validated with solution from Newton-Raphson method.